Does 75% of the difference between VO2 at lactate threshold and VO2max lie at the severe-intensity domain in well-trained cyclists? - Caputo, F. [UNESP]; Denadai, B. S. [UNESP] (Elsevier France-editions Scientifiques Medicales Elsevier, 2009)
Aims. - The purpose of this study was to compare the critical power (CP) with exercise intensities measured as a percentage of the difference between VO2 at lactate threshold (LT) and maximal oxygen uptake (VO2max) (25, 50 and 75%Delta) in well-trained cyclists.Methods. - After determination of the LT and VO2max, 14 mate endurance cyclists performed three constant work rate tests to exhaustion to determine CP.Results. - VO2 (ml. kg(-1) min(-1)) at CP (59.9 +/- 6.6) was significant higher than VO2 corresponding to 25 (50.4 +/- 6.9) and 50%Delta (55.3 +/- 6.5). There was no significantly difference between VO2 at CP and VO2 corresponding to 75%Delta (60.1 +/- 6.2).Conclusions. - It was concluded that researchers intending to explore the responses of well-trained cyclists in the severe-intensity domain have to set exercise intensities higher than 75%Delta. (C) 2009 Elsevier Masson SAS. All rights reserved.
Keywords: Critical power; Cycling; Lactate; Aerobic training